Two-year outcomes of UK patients newly diagnosed with atrial fibrillation: findings from the prospective observational cohort study GARFIELD-AF - Apenteng, PN; Virdone, S; Hobbs, FR; Camm, AJ; Fox, KA; Pieper, KS; Kayani, G; Fitzmaurice, D (Royal College of General Practitioners, 2022)
Background The outcomes of patients newly diagnosed with atrial fibrillation (AF) following the introduction of direct-acting oral anticoagulants are not well known. Aim To determine the 2-year outcomes of patients newly diagnosed with AF, and the effectiveness of oral anticoagulants in everyday practice. Design and setting This was a prospective observational cohort study in UK primary care. Method In total, 3574 patients aged ≥18 years with a new AF diagnosis were enrolled. A propensity score was applied using an overlap weighting scheme to obtain unbiased estimates of the treatment effect of anticoagulation versus no anticoagulation on the occurrence of death, non-haemorrhagic stroke/systemic embolism, and major bleeding within 2 years of diagnosis. Results Overall, 65.8% received anticoagulant therapy, 20.8% received an antiplatelet only, and 13.4% received neither. During the study period, the overall incidence rates of all-cause mortality, non-haemorrhagic stroke/systemic embolism, and major bleeding were 4.15 (95% confidence interval [CI] = 3.69 to 4.65), 1.45 (95% CI = 1.19 to 1.77), and 1.21 (95% CI = 0.97 to 1.50) per 100 person–years, respectively. Anticoagulation treatment compared with no anticoagulation treatment was associated with significantly lower all-cause mortality adjusted hazard ratio (aHR) 0.70 (95% CI = 0.53 to 0.93), significantly lower risk of non-haemorrhagic stroke/systemic embolism (aHR 0.39, 95% CI = 0.24 to 0.62), and a non-significant higher risk of major bleeding (aHR 1.31, 95% CI = 0.77 to 2.24). Conclusion The data support a benefit of anticoagulation in reducing stroke and death, without an increased risk of a major bleed in patients with new-onset AF. Anticoagulation treatment in patients at high risk of stroke who are not receiving anticoagulation may further improve outcomes.